The Influence of Regional Original Income on Economic Growth in the Province of North Sumatera - Novia, Nopia Indah Sari Simamora (Outline Publisher, 2023)
This study aims to determine the effect of Regional Original Income on Economic Growth in the Province of North Sumatra. This study uses quantitative descriptive research because the researcher wants to examine the possibility of a causal relationship between certain factors that may be the cause of the symptoms being investigated. While the nature is explanatory research. The data in the study were obtained from the Central Statistics Agency (BPS) of North Sumatra Province in the 2017-2021 time series. And then the data was processed using an analytical tool, namely the Eviews 10 application with an analytical method, namely simple linear regression analysis. This analysis includes descriptive statistics, classical assumption test, test hypothesis test and f test and the coefficient of determination. The results of the analysis show that both partially and simultaneously, Regional Original Income has a positive and insignificant effect on Economic Growth in North Sumatra Province.